Pelatihan Akademik Dasar Keislaman sebagai Upaya Penguatan Kapasitas Mahasiswa Calon Guru di STIT Al Mubarok - Fadhil Nur Hidayat; M Choirul Muzaini; Syahrul Aziz (LPPM-IAI Hidayatullah Batam, 2026)
This community service initiative aims to strengthen the capacity of final-year students—prospective teachers and administrators of Islamic education—at the Al Mubarok College of Islamic Education (STIT) in Bandar Mataram through basic Islamic academic training. The activity was conducted in the form of a two-day Ramadhan Camp workshop (March 13–14, 2026) with 58 eighth-semester students from the Islamic Education (PAI), Elementary Madrasah Teacher Education (PGMI), and Islamic Education Management (MPI) programs. Training materials included thoharah and prayer practice, women’s issues (masalatunnisa’), funeral preparations (tajhizul janaiz), Hajj and Umrah, and zakat. The methods used were participatory approaches such as demonstrations, paired practice, simulations, Focus Group Discussions (FGDs), and case studies. Evaluation was conducted through participatory observation, discussion dynamics, and feedback provided by the students. The results indicate that this workshop successfully transformed participants’ understanding from theoretical knowledge into solid procedural skills, with FGDs proven effective for sensitive topics as they fostered an inclusive discussion environment. The psychological impact of the training included increased self-confidence among participants as prospective graduates ready to serve as community references in religious practices—as part of an Islamic-based university’s alumni—as well as the development of brotherhood and inter-departmental collaboration. In conclusion, the Ramadhan Camp workshop is effective in equipping final-semester students with basic fiqh skills in the form of practical worship. It is recommended that follow-up programs be implemented, such as community internships, an extension of the training duration, and making this activity a mandatory annual agenda for eighth-semester students.